'CHRIST, OUR LEONIDAS': DRACONTIUS' RECEPTION OF THE BATTLE OF THERMOPYLAE. (29th March 2016) - Murray, Jeffrey
Abstract : One of the final images of Zack Snyder's 2006 box-office-hit film, 300, is of Leonidas, the Spartan king, lying dead on the ground surrounded by his fellow Spartans, having been shot to death by a vast number of Persian arrows. The camera pans over the bruised and bloodied Spartan dead until it finally comes to rest on Leonidas himself, his arms spread out in a gesture that curiously imitates the iconography of the crucifixion of Christ. Whether done explicitly or not, this is not the only time in its reception history that the story of Leonidas' last stand has been linked with Christ's sacrifice on the cross, or with Christianity more generally. In this article, I will explore some aspects of the story of the battle of Thermopylae's reception by the Carthaginian Christian poet Dracontius.